2014
DOI: 10.1104/pp.113.233429
|View full text |Cite
|
Sign up to set email alerts
|

Apyrase Suppression Raises Extracellular ATP Levels and Induces Gene Expression and Cell Wall Changes Characteristic of Stress Responses      

Abstract: Plant cells release ATP into their extracellular matrix as they grow, and extracellular ATP (eATP) can modulate the rate of cell growth in diverse tissues. Two closely related apyrases (APYs) in Arabidopsis (Arabidopsis thaliana), APY1 and APY2, function, in part, to control the concentration of eATP. The expression of APY1/APY2 can be inhibited by RNA interference, and this suppression leads to an increase in the concentration of eATP in the extracellular medium and severely reduces growth. To clarify how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 70 publications
2
98
0
Order By: Relevance
“…Choi et al (2014) revealed that treatment with exogenous 100 µm ATP for 5-60 min increased the expression of mitogenactivated protein kinases, which have been reported to be induced by wounding, herbivore attack, or pathogen infection and be involved in herbivore and pathogen resistance (Zhang & Klessig 1998;Menke et al 2004;Heinrich et al 2011). Correspondingly, by suppressing the expression of apyrase that functions in hydrolysing eATP, it is found that a slight enhancement of the eATP concentration for 3-6 days induced the accumulation of ROS, biosynthesis of lignin, and expression of several genes that are involved in the defence responses to insect herbivores or pathogens (Lim et al 2014).…”
Section: Potential Role Of Eatp In the Defence Responses To Herbivoresmentioning
confidence: 96%
See 3 more Smart Citations
“…Choi et al (2014) revealed that treatment with exogenous 100 µm ATP for 5-60 min increased the expression of mitogenactivated protein kinases, which have been reported to be induced by wounding, herbivore attack, or pathogen infection and be involved in herbivore and pathogen resistance (Zhang & Klessig 1998;Menke et al 2004;Heinrich et al 2011). Correspondingly, by suppressing the expression of apyrase that functions in hydrolysing eATP, it is found that a slight enhancement of the eATP concentration for 3-6 days induced the accumulation of ROS, biosynthesis of lignin, and expression of several genes that are involved in the defence responses to insect herbivores or pathogens (Lim et al 2014).…”
Section: Potential Role Of Eatp In the Defence Responses To Herbivoresmentioning
confidence: 96%
“…As mentioned above, short-term or slight enhancements of eATP level seem to induce some physiological responses that are also induced by or are associated with the defence responses to pathogen (Song et al 2006;Lim et al 2014). Thus, eATP could serve as an early signal of plant defence responses to pathogen infection.…”
Section: Plant Defence Responses To Pathogens and Eatpmentioning
confidence: 99%
See 2 more Smart Citations
“…A dozen studies showed that extracellular ATP signaling is associated with second messengers-cytosolic calcium (Ca 2+ ), reactive oxygen species (ROS), and nitric oxide (NO; Demidchik et al, 2003;Jeter et al, 2004;Song et al, 2006;Foresi et al, 2007;Wu and Wu, 2008;Reichler et al, 2009;Tanaka et al, 2010b;Tonón et al, 2010;Clark et al, 2011;Sun et al, 2012;Lim et al, 2014). Some of them are suggested to be mediated by cellular components in the plasma membrane, including Ca 2+ channels, heterotrimeric G Proteins, and NADPH oxidase (Song et al, 2006;Demidchik et al, 2009;Weerasinghe et al, 2009;Tanaka et al, 2010b;Hao et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%